The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.physbeh.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute stress on human prefrontal working memory systems

Abstract: We examined the relationship between acute stress and prefrontal-cortex (PFC) based working memory (WM) systems using behavioral (Experiment 1) and functional magnetic resonance imaging (fMRI; Experiment 2) paradigms. Subjects performed a delayed-response item-recognition task, with alternating blocks of high and low WM demand trials. During scanning, participants performed this task under three stress conditions: cold stress (induced by cold-water hand-immersion), a room temperature water control (induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 63 publications
10
67
1
2
Order By: Relevance
“…Consistent with the beneficial effect of cortisol in young participants, inhibition of cortisol synthesis in older human subjects has been found to impair memory, which is reversed by restoring normal cortisol levels (27). The increased excitatory synaptic strength of PFC pyramidal neurons revealed in our study could also underlie the acute stress-elicited increase in PFC activity revealed from fMRI studies of human subjects (28), which is thought to be necessary to mediate cognitive processes for maintaining organized and complex human behavior.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with the beneficial effect of cortisol in young participants, inhibition of cortisol synthesis in older human subjects has been found to impair memory, which is reversed by restoring normal cortisol levels (27). The increased excitatory synaptic strength of PFC pyramidal neurons revealed in our study could also underlie the acute stress-elicited increase in PFC activity revealed from fMRI studies of human subjects (28), which is thought to be necessary to mediate cognitive processes for maintaining organized and complex human behavior.…”
Section: Discussionsupporting
confidence: 83%
“…Event-related functional magnetic resonance imaging (fMRI) was used to capture potential neural correlates of memory phase-dependent effects of stress in the human brain. Based on the previous literature [Porcelli et al, 2008;Qin et al, 2009], we expected that stressed and nonstressed participants would differ in neural activity in areas related to WM maintenance [PFC and posterior parietal cortex (PPC); Fletcher and Henson, 2001;Purves et al, 2008]. We further hypothesised that stressed participants would show an increase in hippocampal activity during memory encoding, corresponding to improved encoding and subsequent memory previously reported for declarative memory tasks [Otten et al, 2001].…”
Section: Introductionmentioning
confidence: 87%
“…It has also been shown that one of the brain areas in humans affected by stress is the prefrontal cortex (8). As a matter of fact, studies carried out using functional brain imaging show that some parts of the prefrontal cortex are engaged in many tasks related to working memory and basic cognitive functions, such as attention and task management.…”
Section: Introductionmentioning
confidence: 99%